India-China Supply Chain - Chaudhary, Deepanshu (2015)
Waterways have formed to be an important segment in enhancing sea trade on an international basis. Moreover, it is quite logical to state that there should be an integration of each system of transportation in order to make the port and terminal transportation successful. Here, ports and terminals of India have to be studied when a need of presenting a national identity arises at an international stage. The working of the port is dependent on the levels of ports and how they utilize the resources and therefore make alterations and changes in the infrastructure. It is also required to consider the requirement of reformation, which will lead to a futuristic reformation. Supply chain is observed as a source of competitive advantage over its competitors. Whereas most of the Indian companies have very low involvement in supply chain processes. Even the detailed examination on India- China trade was conducted to measure the effectiveness of supply chain in the literature review. The main focus of research was on the secondary research and a bit of primary research is also conducted to know the cost of transportation from JNPT to New Delhi and infrastructural condition of India. The research finding helps in meeting the objectives of the study.